Factors associated with abnormal cerebral blood flow in Egyptian children with sickle cell disease. Issue 1 (12th March 2020) - Abd-Allah, Foad; Eltagui, Mona; Aboulfotooh, Alshaimaa Mahmoud; Kishk, Nirmeen Adel; Farrag, Mohammad Ahmed; Mohammed, Sandra Ahmed; Shamloul, Reham Mohammed; El-Jaafary, Shaimaa; Said, Fadwa; Ibrahim, Ahmed; Elghamrawy, Mona
Background: Transcranial Doppler (TCD) is a well-established tool for cerebrovascular assessment. Estimating the flow velocity across the intracranial arteries helps to identify children with sickle cell anaemia who are at risk for stroke. Objective: Our aim is to correlate TCD findings with clinical condition in children with sickle cell disease (SCD) to determine the value of TCD assessment as a predictive tool for stroke in SCD and to identify any association of TCD findings with disease severity, transfusion therapy and treatment administered. Methods: Eighty-five paediatric SCD patients aged from 3 years to 18 years of both genders who were followed up at the Hematology Clinic of New Children's Hospital at Cairo University were included in this cross-sectional observational study. All our participants underwent routine laboratory investigations and TCD assessments. Results: Oof the 85 patients, two patients (2.3%) died before completing the TCD study and eventually 83 patients were included in the analysis. Seventeen (20.5%) patients had abnormal TCD findings, seven (8.4%) patients showed high-risk findings and 10 (12.1%) patients had conditional flow pattern. Logistic linear regression analysis confirmed that annual frequency of blood transfusion and hydroxyurea (HU) dose were associated with a decreased risk of abnormal TCD findings. Conclusion: The current study demonstrates that our TCD data reproduce the findings of other studies and that it is very likely the results from large trials are applicable for Egyptian children. The annual frequency of blood transfusion and HU dose were associated with a decreased frequency of abnormal TCD findings.